2019
DOI: 10.1080/09581596.2019.1597965
|View full text |Cite
|
Sign up to set email alerts
|

Misdirection in the margins of malaria elimination methods

Abstract: This paper proposes the term misdirection as a process by which attention is diverted from certain scientific approaches in the malaria elimination paradigm to justify specific methodological, scientific and political decisions. Misdirection, as it applies in magic, creates a sort of tunnel vision in which attention is diverted away from any action occurring outside the frame of the current paradigm. A crucial component of this misdirection process is the global standardization of intervention methodologies op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Our findings highlight that even within an environment which fosters trust in biomedical interventions and wherein communities are engaged, tensions can still exist between biomedical rationale of implementing an intervention (i.e., designing a more targeted contextualized intervention for impact on malaria transmission) with community interests (i.e., in terms of addressing their perception of malaria risk to beyond defined boundaries). Addressing this issue, requires the continuous use of co-creative systemic research approaches (29), which acknowledges that community members and researchers both bring valuable insights during the research process, and that knowledge ought to be generated collaboratively (67). Community members have detailed knowledge on their contextual realities that shape their risk perceptions, whilst researchers contribute toward the research methods and methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings highlight that even within an environment which fosters trust in biomedical interventions and wherein communities are engaged, tensions can still exist between biomedical rationale of implementing an intervention (i.e., designing a more targeted contextualized intervention for impact on malaria transmission) with community interests (i.e., in terms of addressing their perception of malaria risk to beyond defined boundaries). Addressing this issue, requires the continuous use of co-creative systemic research approaches (29), which acknowledges that community members and researchers both bring valuable insights during the research process, and that knowledge ought to be generated collaboratively (67). Community members have detailed knowledge on their contextual realities that shape their risk perceptions, whilst researchers contribute toward the research methods and methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the current dominant scientific paradigm of standardized households may shadow alternative contextualized solutions which addresses the realities of the concept of the household (29,30). To date, household definitions remain influenced by the United Nations (UN) household guidelines for census enumerations based on the three main criteria of (i) residence (i.e., living together/sleeping under the same roof); (ii) housekeeping (i.e., pooling of resources), and (iii) provision of food (i.e., eating from the same pot).…”
Section: The Study Protocol and Related Assumptionsmentioning
confidence: 99%
“…In this paper, we have conducted an epistemic audit of what is gained and what is lost in the current state of play of global public health knowledge about fake drugs. We have considered what the larger epistemic effects of these persistent evidence gaps might be and concluded that these evidence gaps actually function as a ghost in the data that might be misdirecting attention (Peeters Grietens et al, 2019 ). This matters because by generating more data and highlighting absences we are hindered from understanding the power dynamics that condition how we know fakes, such as how quality assurance data (or, indeed its absence) structures the contemporary political economy of pharmaceuticals within global health.…”
Section: Conclusion: the Ghost In The Datamentioning
confidence: 99%
“…We argue that the upshot of the persistent mismatch between bold claims and weak evidence is to frame fake drugs as an unknowable problem. Rendering fake drugs as unknowable matters, we argue, because it misdirects (Peeters Grietens et al, 2019 ) attention away from the conditions that produce drugs’ unknowability – that is, the structural conditions that shape what we know and the ‘closed shop’ that is the pharmaceutical industry's approach to their own data (Sismondo, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these collaborative efforts and control measures, tackling malaria remains challenging due to regional complexities such as the uneven distribution of malaria cases, the biodiversity of vectors, heterogeneous human and vector behaviour (1,5,6,9,17,18), the spread of drug resistance (6,9,19), remaining poor accessibility (5,9), and high population mobility, including cross-border movements into areas of higher malaria incidence (5,9,20). Moreover, the uncritical application of standardised measures in diverse ethno-socio-cultural contexts ignores social parameters, generating pseudo outcomes, real in their adherence to standardised methods and fake in the applicability of the conclusions it draws for local populations (21,22). In the GMS, the inhabitants of forested areas originate from diverse ethnic minorities who respectively engage in speci c economic activities.…”
mentioning
confidence: 99%